Depression in Adolescence: Examining the Role of School Engagement and Parental Support - Ishita Kapur; Jennifer Murphy (International Journal of School Social Work, 2024)
Substantial research evidence indicates depression in adolescence leads to severe impairments in daily life and affects later life outcomes. The consequences of adolescent depression can adversely impact adolescents’ relationship with parents and academic outcomes. Therefore, this study examines the impact of school experiences with the moderating role of parental support on the reporting of major depressive episodes by adolescents. The study utilized the National Survey of Drug Use and Health (2019) database with a sample of adolescents, ages 12-17 (N=11,595). We conducted a moderation analysis to study the impact of school experience on major depressive episodes in adolescents with parental support as our moderating variable. Both school experience and parental support had a significant impact on the reporting of adolescent depression, parental support was found to have a lesser impact on the reporting of adolescent depression compared to school experience. Results also showed the odds of reporting major depressive episodes by adolescents decreased with every year increase in age. Females reported higher major depressive episodes in comparison to males. Results of this study suggest the race category of Black adolescents reported increased depression in comparison to the White population. Findings suggest understudied factors such as race leads to poor reporting of mental health outcomes in adolescents. Interventions at the level of schools and parents are needed that target the prevention and increased reporting of adolescent depression.
Keywords: Depression; adolescents; schools; parents; support